ANALISIS KEPADATAN NYAMUK MENGGUNAKAN LIGHT TRAP PADA KEJADIAN MALARIA - Husin, Hasan (JURNAL MEDIA KESEHATAN, 2017)
Light Trap is a mosquito catcher by using light to trap mosquito into a research container. The study objective was to find out the relationship between the density of anopheles mosquitoes with malaria incidence in Taba Lagan Village, Central Bengkulu. This research is quasi-experiment with quantitative approach. The population of this study was all of mosquitos breeding place data and all of patients data who got treatment at community health centre of Tabalagan. Samples of the study were selected by using proportional random sampling. The results showed that the density of mosquitoes about 127 in cowshed which had some characteristics such as bigger size than another mosquito and they used to come out about 06.00 to 10.00 PM. There were 96 medium-sized mosquitoes at rubber plantation which had activity around 05.00 AM. While there were 38 small-sized mosquitoes which are living around cluster residents environment and usually bit human about 06.00 to 09.00 PM. In concluding, the largest number of anopheles mosquitoes was in cowshed (0.118%) with malaria cases of 6 people and who are living about 10 to 20 meters nearby cowshed.